Multi Criteria Decision Making for the Preparation of Sustainability Indicators for the Printing Sector Industry - Agusti, Febrina; Buwono, Ringgo Ismoyo; Dwyanton, Fertilio; Wahyono, Adit Tri (Universitas Diponegoro, 2025)
The government encourages industry players to continue to innovate and be sustainable in accordance with the commitment of the Ministry of Industry of the Republic of Indonesia. Industrial sustainability itself requires careful planning such as indicators and strategy formulation. Currently, the large number of industries in various sectors has given rise to fierce competition. The printing industry sector was an industry with significant development of 10 percent since 2019-2024. The purpose of this study was to develop indicators of industrial sustainability that were implemented in the printing sector in Surakarta City. The methods used were the Delphi Method and the Multi-Criteria Decision Making (MCDM) Method. The respondents of this study were PT Margo Mitro Joyo and PT Putra Nugraha Sentosa. The results of the study can produce 22 indicators of industrial sustainability, while also determining the level of sustainability of the printing sector industry in Surakarta in the good category.